2012
DOI: 10.1371/journal.pone.0047994
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-Akt Immunoreactivity in Prostate Cancer: Relationship to Disease Severity and Outcome, Ki67 and Phosphorylated EGFR Expression

Abstract: BackgroundIn the present study, we have investigated the prognostic usefulness of phosphorylated Akt immunoreactivity (pAkt-IR) in prostate cancer using a well-characterised tissue microarray from men who had undergone transurethral resection due to lower urinary tract symptoms.Methodology/Principal FindingspAkt-IR in prostate epithelial and tumour cells was assessed using a monoclonal anti-pAkt (Ser473) antibody. Immunoreactive intensity was determined for 282 (tumour) and 240 (non-mlignant tissue) cases. Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Phosphorylation of Thr308 on Akt is activated by PDK1 [81], while the phosphorylation of serine 473 on Akt is activated by mTOR kinase, its associated protein rector, and SIN1/MIP1 [82, 83]. Akt phosphorylation level correlates with higher Gleason score [84, 85]. CAPE treatment caused mild but dose-dependent repression of Akt1, Akt2, as well as phosphorylation of Akt and PDK1 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Thr308 on Akt is activated by PDK1 [81], while the phosphorylation of serine 473 on Akt is activated by mTOR kinase, its associated protein rector, and SIN1/MIP1 [82, 83]. Akt phosphorylation level correlates with higher Gleason score [84, 85]. CAPE treatment caused mild but dose-dependent repression of Akt1, Akt2, as well as phosphorylation of Akt and PDK1 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…AKT phosphorylated at Ser473 or Thr308. Moreover, expression of activated AKT has been shown to be associated with a worse outcome in a wide variety of cancers, including cancers of the lung [20], head and neck [21], breast [22,23], brain [24], prostate [25,26], and pancreas [27,28]. However, some studies have reported opposite correlations, whereby high levels of phosphorylated AKT were correlated with a better outcome [29,30].…”
Section: Pi3-k/akt Pathway and Clinical Outcomementioning
confidence: 99%
“…Simvastatin also induced apoptosis in prostate cancer cells via simultaneous modulation of intrinsic cell survival and extrinsic apoptotic pathways (Goc et al, 2012b). Simvastatin-induced effects on prostate cancer cells were mainly mediated through the inhibition of Akt, a serine-threonine kinase that has been implicated to be essential for prostate cancer progression and metastasis (Hammarsten et al, 2012, Goc et al, 2011, Goc et al, 2012d). Our studies have also demonstrated the pivotal role of Akt in mediating prostate cancer micrometastasis via activation of integrin α v β 3 (Goc et al, 2012d), which have been reported to be elevated in prostate cancer cells (McCabe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%